2021
DOI: 10.1007/s42235-021-0038-7
|View full text |Cite
|
Sign up to set email alerts
|

Smart Bionic Surfaces with Switchable Wettability and Applications

Abstract: In order to satisfy the needs of different applications and more complex intelligent devices, smart control of surface wettability will be necessary and desirable, which gradually become a hot spot and focus in the field of interface wetting. Herein, we review interfacial wetting states related to switchable wettability on superwettable materials, including several classical wetting models and liquid adhesive behaviors based on the surface of natural creatures with special wettability. This review mainly focus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 179 publications
(224 reference statements)
0
10
0
Order By: Relevance
“…A typical example involves the conversion of organic carbonates 270 and formylation of alkenes 271 among many other catalytic systems. 236,272,273 Magnetic separation techniques can be also effectively employed for the development of magnetically recoverable catalysts in ILs. 274 These can be accomplished by use of paramagnetic IL-coated nanoparticles 275 or magnetic nanoparticles in ILs.…”
Section: External Physical Stimuli-smart Ilsmentioning
confidence: 99%
See 1 more Smart Citation
“…A typical example involves the conversion of organic carbonates 270 and formylation of alkenes 271 among many other catalytic systems. 236,272,273 Magnetic separation techniques can be also effectively employed for the development of magnetically recoverable catalysts in ILs. 274 These can be accomplished by use of paramagnetic IL-coated nanoparticles 275 or magnetic nanoparticles in ILs.…”
Section: External Physical Stimuli-smart Ilsmentioning
confidence: 99%
“…A typical example involves the conversion of organic carbonates 270 and formylation of alkenes 271 among many other catalytic systems. 236,272,273…”
Section: Separation Of Substrates/products From the Catalytic Phasementioning
confidence: 99%
“…The development of biomedical materials currently needs extremely high standards in terms of functionality, bioactivity, and biocompatibility. Scientists have made sincere efforts [2] to partially or completely meet these criteria using a variety of techniques. The most promising among them have been biomimetic or bioinspired [3] since the compounds, architectures, and processes of living organisms display nature-based, time-tested approaches for obtaining desirable material properties.…”
Section: Introductionmentioning
confidence: 99%
“…As a matter of fact, surface wettability has a profound effect on other properties of solid surfaces, for example self-cleaning, antifouling, oil-water separation, anti-fog capabilities, etc. Inspired by natural surfaces such as rose petals, lotus leaves, nepenthes slippery, mosquito compound eyes, rice leaves, water striders, etc., 1 researchers have found that natural surfaces mainly rely on the synergistic effect of the chemical composition and surface morphology to achieve superwetting behavior. 2,3 In fact, surfaces with fixed wettability cannot meet complex practical applications.…”
Section: Introductionmentioning
confidence: 99%
“…Properties of random copolymers with different sulfonation ratios and their modified surfaces In the sulfonation reaction, the feed molar ratio of 1,3-PS to DMAEMA. b The actual sulfonation ratios of PDDQ determined by1 H NMR with thecalculation equation of m bulk ¼ S m =6 ðS m =6Þ þ ðS e =2ÞÂ 100%. c The surface sulfonation ratios determined by XPS with the calculation equation of…”
mentioning
confidence: 99%